Akuntabilitas Kecepatan dan Ketepatan Penggunaan APD Desa di Desa Pakijangan dan Karangjatianyar, Wonorejo, Pasuruan - Devi Ika Irawati; Cakti Indra Gunawan; Cahyo Sasmito (Fakultas Ekonomi Universitas Panca Marga, 2023)
The village as the smallest government system needs to manage its finances properly to support village development and improve people's welfare. This study aims to describe and analyze the mechanisms, factors, and models for implementing village Treasurer and Operator accountability to increase the speed and accuracy of using Village Budgets in Pakijangan Village and Karangjatianyar Village, Wonorejo District, Pasuruan Regency. This study uses a qualitative method by collecting primary and secondary data directly on the Village treasurer and Operators from January to March 2022. The results of this study are that the mechanism for implementing accountability by Village treasurer and Operators is carried out by fulfilling 5 (five) dimensions, namely transparency, accountability, control, responsibility, and responsiveness. Supporting factors are timely village financial reporting, transparency and accountability for village financial management while inhibiting factors are the lack of understanding of village officials in village financial reporting and frequent changes in village officials. The accountability model for using the Village Budget in Pakijangan Village and Karangjatianyar Village involves the role of the Camat, Village Government, and General Binwas Parties, by carrying out evaluations. Suggestions for future researchers are to discuss the components of village financial management in detail.